Antioxidant and lipid peroxidation status in the blood of patients with active vitiligo - Naziro?lu, Ibrahim Kökçam Mustafa; Imşek, Halil; Aydilek, Nurettin; Uyar, Belkis (My University, 1999)
The aim of this research was to determine blood levels of vitamin E, beta-carotene, lipid peroxidation as malondialdehyde (MDA), reduced glutathione (GSH), and glutathione peroxidase (GSH-Px) activity in patients with active endogenous vitiligo (PAV). Studies were carried out in 23 patients with different types of active vitiligo and healthy age-matched controls. Erythrocytes and plasma samples from both groups were taken. GSH levels and activity of GSH-Px in both plasma and erythrocyte samples were significantly lower, whereas MDA levels in the erythrocyte samples were significantly higher in PAV than in controls. However, vitamin E, beta- carotene, and MDA in plasma samples did not differ statistically. In conclusion, levels of MDA in plasma and erythrocyte samples were increased in PAV, whereas plasma and erythrocyte GSH-Px activities were decreased. These results are discussed on the basis of occupational leukoderma vitiligo.
Keywords: Antioxidants; Beta-carotene; Lipid peroxidation; Vitamin E; Vitiligo